HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DAN KELENTUKAN PUNGGUNG TERHADAP KEMAMPUAN SERVIS ATAS EKSTRAKURIKULER BOLA VOLI PUTRA SMP NEGERI 27 PEKANBARU - Andayani, Yuyun; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem with this research is still a lack of ability back up in a vollyball game the students of smp negeri 27 pekanbaru, this is beceause the flexibility the back is less than the maximum. To boost and create the service for in the in a volleyball game, then take a few element of it is a technique,flexibility,strength, so it could affeect the ability to serve on the vollyball. Research this a correlation the aim to know the relationship between variabeles and are tied. After that, the data normality test with Liliefors test with significance level Î± = 0.05, and gained normality test results X1, Lomax (0.205) <Ltabel(0,242) and X2 Lomax (0.144) <Ltabel (0,242) test normality variable Y, Lomax (0.204) <Ltabel (0,242) in other words the normal distribution of data. Then proceed to determine r by using product moment correlation analysis, , if rhitung<rtabel then there is a significant relationship, the result show there is a significant connetion between the power arm muscles and shoulders and flexciblity the back of the service for vollyball. Thus the conclusion there is a significant connection between the power arm muscles and shoulders and flexciblty the back of the service for extracurricular volleyball in the smp negeri 27 pekanbaru.Based on the analysis can explain that the results of this study shows that there are positive relationships between the power arm muscles and shoulders and flexciblty the back of the service.Key Words: The power of the dab the shoulder, flexcbility the back, the service for.